Implementation of Network Mapper Tools on Local Area Networks - Miftah Fauzy Alvaruqi; Jajam Haerul Jaman (Peneliti.net, 2022)
The development of computer technology in today's rapidly increasing, a lot of aspects in the world of computers that can be developedstarting from the hardware ( hardware ) , software ( software ) as well as its operating system . Almost every year , every month , even every week of ering computer world discoveries and developments bothhardware ( hardware ) and software (the software) . The development of software on the network world is something that is very encouraging for network users , a wide range of specializedsoftware for a network marketed by the manufacturer ofthe software , but of development - these developments there is the other side that we do not want, which exploit program development , as this can be detrimental to network users , we can imaginehow disappointed we are , when we are indulge in the network and find out the data - welost important data , or classified documents we are known by people who are not responsible , users exploit program is known as hackers , Tools Network Mapper is one of the many programs exploit in the world. Tools Network Mapper program called the exploit because it can be used to identify in and explores the data without the knowledge of thetarget computer or computer without the user'spermission on the go , therefore we should be more careful - be active in the network. we already know that in order to solve a problem properly we must first study the problem itself, from the emergence of the problem until thecause and ef ect that caused by the problem itself , as well as in the manufacture of network security software , of course, the software maker first study one or a few programs - programs that exploit exists. In connection with our society is still relatively ignorant about theexploit in the writing program faculty research , the writer willdiscuss about the workings of oneof the programs that exploit Tools Network Mapper in identifying in and explores the target computer data.